(untitled) (Alternautas, 2022)
In 2018 the Albert Hirschman Centre on Democracy in Geneva organized together with Europaeum and Alternautas, the workshop on “Democracy, Indigenous Rights and Ethno-Racial Mobilization: Latin America in Comparative Perspective.” This workshop was part of the “Geneva Democracy Week” organized by the Geneva Chancellery of State to promote dialogue between political institutions, civil society, students and citizens, with a view to strengthening their participation in democratic processes. Our focus on Indigenous and Afrodescendant movements was intended to illuminate the ongoing contributions these populations have made to expanding and redefining democracy. Latin America has been the site of inspiring activism over the last decades, as formerly subaltern populations have challenged the ongoing legacies of colonialism and claimed citizenship rights. We received paper proposals from students of different European universities in Switzerland, England, Germany and Luxemburg and selected nine papers to be discussed at the workshop on the 6th of October at the Graduate Institute of International and Development Studies. The papers received feedback from the workshop conveners, Graziella Moraes, Filipe Calvão and Diego Silva from the Graduate Institute in Geneva, as well as from our special guests Nancy Postero, professor UC San Diego, Ethel Branch, former Attorney General of the Navajo Nation and Karen Ramirez Bóscan, founder of Wayunkerra Indigenous Women’s Initiative in Guajira Colombia, as well as anonymous peer review. Thus, the articles in this special issue of Alternautas are the product of a rich international conversation.